Rediscounting under aggregate risk with moral hazard - James T. E. Chapman; Antoine Martin (Bank of Canada, 2007)
Freeman (1999) proposes a model in which discount window lending and open market operations have different effects. This is important because in most of the literature, these policies are indistinguishable. However, Freeman's argument that the central bank should absorb losses associated with default to provide risk-sharing stands in stark contrast to the concern that central banks should limit their exposure to credit risk. We extend Freeman's model by introducing moral hazard. With moral hazard, the central bank should avoid absorbing losses and Freeman's argument breaks down. However, we show that policies resembling discount window lending and open market operations can still be distinguished in this new framework. The optimal policy is for the central bank to make a restricted number of creditors compete for funds. By restricting the number of agents, the central bank can limit the moral hazard problem. By making them compete with each other, the central bank can exploit market information that reveals the state of the economy.
Keywords: G20; E58; 330; Payment; clearing; and settlement systems; Financial markets; Central bank research; Gesamtwirtschaftliche Liquidität; Zentralbank; Offenmarktpolitik; Diskontpolitik; Kreditrisiko; Moral Hazard; Theorie